КОМП'ЮТЕРНЕ МОДЕЛЮВАННЯ ЕЛЕКТРИЧНИХ ПРОЦЕСІВ ПІД ЧАС ВИНИКНЕННЯ ЧАСТКОВИХ РОЗРЯДІВ У СУЧАСНІЙ ПОЛІМЕРНІЙ ІЗОЛЯЦІЇ СИЛОВИХ КАБЕЛІВ - Щерба, А.А.; Подольцев, О.Д.; Гуторова, М.С. (Інститут електродинаміки НАН України, Київ, 2024)
A Simulink model of modern polymer insulation of power cables with a spherical gas micro-inclusion, in which high-frequency partial discharges (PDs) occur, has been developed. The magnitude of the voltage both at the beginning of the PD appearance and during its decay was taken into account during numerical calculations and research of such threshold electro-physical processes as PD in solid polymer insulation. The dependence of the voltage drop on the gas micro-inclusion on its size, as well as the time interval between discharges, which is necessary for the formation of free electrons in this gas micro-inclusion, as a necessary condition for the appearance of the next PD, was also taken into account. Based on the results of the calculations, the electro-physical dependences that occur during the PD, such as the influence of the size of the inclusion, the amplitude and frequency of the applied sinusoidal voltage on the above-mentioned characteristics were investigated. It has been revealed that with an increase in the diameter d of a gas microinclusion, such characteristics as the number of discharges per period and the charge of one PD also increase, and this charge increases in proportion to a power function . When the voltage on the cable insulation increases, the number of PDs per period increases, which causes an increase in other characteristics, and when the frequency of the applied voltage increases, the average value of the PDs current increases almost proportionally to the increase in this frequency. Having obtained the results of the calculation of the level of PDs that occur when high-frequency voltage is applied, it is possible to obtain results for the main characteristics of PDs that occur at other frequencies, in particular at the industrial frequency of 50 Hz, which will make it possible to predict the technical condition of the insulation in terms of the residual resource of its trouble-free operation. References 18, figures 6, table 1.